About the Actual Division of the Sentence and Word Order - Anvar Kuvandikovich, Sobirov (International Journal of Psychosocial Rehabilitation, 2020)
This article explores the relevance and vocabulary of sentences in Russian and Uzbek linguistics. In the work, the actual division of the sentence and the order of the word are considered, and the actual division of the sentence has been studied in relation to the order of words as an important communicative-syntactic phenomenon. Adding to some linguists’ arguments that the actual division of a sentence is like a division of a sentence (a division of a subject and a predicate) into a logical unit, the actual division is called a logicalgrammatical division. Important topicals: prosodic actuator (logical accent and related speech pace and pause), emphatic-emotional emphasis (emotionally intense, vowel or consonant), lexical and grammatical actualization (only, alone, even; the words themselves, and only, -with, -with the addition).